2020
DOI: 10.1002/ajh.25781
|View full text |Cite
|
Sign up to set email alerts
|

Microtransplantation in older patients with AML: A pilot study of safety, efficacy and immunologic effects

Abstract: Older AML patients have low remission rates and poor survival outcomes with standard chemotherapy. Microtransplantation (MST) refers to infusion of allogeneic hematopoietic stem cells without substantial engraftment. MST has been shown to improve clinical outcomes compared with chemotherapy alone. This is the first trial reporting on broad correlative studies to define immunologic mechanisms of action of MST in older AML patients. Older patients with newly diagnosed AML were eligible for enrollment, receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Sung et al. also reported an incidence of HLA-mismatched stem cell transplantation-related CRS of 40%, of which most cases were mild ( 62 ). There is currently no recognized term for this CRS, and we therefore referred to it as “post-TLI CRS”.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Sung et al. also reported an incidence of HLA-mismatched stem cell transplantation-related CRS of 40%, of which most cases were mild ( 62 ). There is currently no recognized term for this CRS, and we therefore referred to it as “post-TLI CRS”.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, HLAmismatched HSCT-related CRS was proposed as early as 2009 in a study of non-engraftment haploidentical cellular immunotherapy, termed "haplo immunostorm", which presents with a series of clinical symptoms accompanied by cytokine flux, and has been shown to be sensitive to steroids (67). Sung et al also reported an incidence of HLA-mismatched stem cell transplantation-related CRS of 40%, of which most cases were mild (62). There is currently no recognized term for this CRS, and we therefore referred to it as "post-TLI CRS".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microtransplantation is an HLA-mismatched granulocyte colony-stimulating factor-mobilized donor peripheral blood stem-cell infusion, without HLA-restriction. At present, it has been reported that microtransplantation can improve the overall survival of elderly AML patients who cannot undergo HSCT, and shows high tolerance and low severe toxicity ( 10 , [12] , [13] , [14] , [15] ). A multicenter clinical study found a high CR rate (74.6%) in AML patients aged 60 to 85 years after microtransplantation, with 1.1% underwent GVHD ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some centres have reported that MST could improve the outcomes of AML patients [15][16][17][18][19][20] . However, other institutions did not nd similar e cacy of MST in treating AML patients [21,22] . Brie y, more studies need to be conducted to validate the e cacy and safety of MST in treating older AML patients.…”
Section: Introductionmentioning
confidence: 99%